Isolation and Functional Analysis of Genes Involved in Polyacylated Anthocyanin Biosynthesis in Blue Senecio cruentus - Lu, Chenfei; Li, Yajun; Cui, Yumeng; Ren, Jiangshan; Qi, Fangting; Qu, Jiaping; Huang, He; Dai, Silan (Frontiers in Plant Science, 2021)
Polyacylated anthocyanins with multiple glycosyl and aromatic acyl groups tend to make flowers display bright and stable blue colours. However, there are few studies on the isolation and functional characterization of genes involved in the polyacylated anthocyanin biosynthesis mechanism, which limits the molecular breeding of truly blue flowers. Senecio cruentus is an important potted ornamental plant, and its blue flowers contain 3',7-polyacylated delphinidin-type anthocyanins that are not reported in any other plants, suggesting that it harbours abundant gene resources for the molecular breeding of blue flowers. In this study, using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) analysis of blue, carmine and white colours of cineraria cultivars ‘Venezia’ (named VeB, VeC and VeW, respectively), we found that 3',7-polyacylated anthocyanin, cinerarin, was the main pigment component that determined the blue colour of ray florets of cineraria. Based on the transcriptome sequencing and differential gene expression (DEG) analysis combined with RT- and qRT-PCR, we found two genes encoding uridine diphosphate glycosyltransferase, named ScUGT1 and ScUGT4; two genes encoding acyl-glucoside-dependent glucosyltransferases which belong to glycoside hydrolase family 1 (GH1), named ScAGGT11 and ScAGGT12; one gene encoding serine carboxypeptidase-like acyltransferase ScSCPL2; and two MYB transcriptional factor genes ScMYB2 and ScMYB4, that were specifically highly expressed in the ray florets of VeB, which indicated that these genes may be involved in cinerarin biosynthesis. The function of ScSCPL2 was analysed by virus-induced gene silencing (VIGS) in cineraria leaves combined with HPLC-MS/MS. ScSCPL2 mainly participated in the 3' and 7- position acylation of cinerarin. These results will provide new insight into the molecular basis of the polyacylated anthocyanin biosynthesis mechanism in higher plants and are of great significance for blue flower molecular breeding of ornamental plants.